Deontic Logic in Computer Science 10th International Conference, DEON 2010, Fiesole, Italy, July 7-9, 2010. Proceedings - Governatori, Guido.; Sartor, Giovanni. (Lecture Notes in Computer Science,, 2010)
This volume presents the refereed proceedings of the 10th International Conference on Deontic Logic in Computer Science, DEON 2010, held in Fiesole, Italy, in July 2010. The 18 revised papers included in the volume were carefully reviewed and selected from 34 submissions. Topics covered include connections preferences, deontic logic and contrary-to-duties, the use of input/output logic, the study of norm dynamics, models of agents and institutions, argumentation, compliance, and various alternative analyses of deontic notions.